3x+1+6x=-89

Simple and best practice solution for 3x+1+6x=-89 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+1+6x=-89 equation:


Simplifying
3x + 1 + 6x = -89

Reorder the terms:
1 + 3x + 6x = -89

Combine like terms: 3x + 6x = 9x
1 + 9x = -89

Solving
1 + 9x = -89

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 9x = -89 + -1

Combine like terms: 1 + -1 = 0
0 + 9x = -89 + -1
9x = -89 + -1

Combine like terms: -89 + -1 = -90
9x = -90

Divide each side by '9'.
x = -10

Simplifying
x = -10

See similar equations:

| 38x+136=x+163 | | 6x+5-5x=10 | | 5t=3(7t) | | -10-2x=6x+2(-7x+7) | | -8+7x+3x=-8 | | x+5-2x= | | Y=100-4n | | -7r+6t-8s-5r+12s+4t-t+2s-11r= | | 3c-3=6 | | -25=a(x-3)+3 | | 12-4x=3x^3-x^2 | | 8x-9x^3+1=0 | | .005x-.07=.02x+.0032 | | 18x^2+21x-49=0 | | 5=2+3s | | 5n+17=8(-8-3n)-6 | | 9-0.1k=9 | | 2-5v=-v+2(1+7v) | | x+5+2x= | | 12-7n=6-8n | | 3(2x+3)=2x+21 | | 59x-(21x+34)=0 | | 28-5n=3(5-8n)-6 | | 2x+15=2y-15 | | 5(x+4)+-4x=18-23 | | -9g-6g-4=-16-16g | | -4(x-4)-6=-7+2(4-2x) | | 3x*2+6x+4800=0 | | y=-16x^2+9x+30 | | -14z+2z-7=-20-11z | | 10t=7y+15 | | 3(1-2x)=7-5x |

Equations solver categories